Development and applications of deep eutectic solvent derived functional materials in chromatographic separation. Issue 6 (5th August 2020) - Li, Linnan; Liu, Yamin; Wang, Zhengtao; Yang, Li; Liu, Huwei
Abstract: Deep eutectic solvents have received increasing attention over the past decade, and the green and versatile nature makes them important media for developing environmentally friendly and sustainable technologies. In addition to act as green alternatives to traditional organic solvents, deep eutectic solvents offer tremendous opportunities to produce different kinds of emerging functional materials. The present review highlights the recent development and applications of deep functional materials based on deep eutectic solvents as novel adsorbents for diverse analytes in complex matrices. The type, preparation, and unique properties of deep eutectic solvents, the synthesis of deep eutectic solvent derived materials, as well as their applications in chromatographic separation are described. We aim to demonstrate that deep eutectic solvents not only allow the design of eco‐friendly extraction processes but also open straightforward access to advanced materials in sample preparation.